The Law of One Price: Evidence from the Transitional Economy of China - Fan, C. Simon; Wei, Xiangdong (The Review of Economics and Statistics, 2006)
This paper applies the recently developed econometric methods of panel unit root tests and nonlinear mean reversion to investigate price convergence in China–the largest transitional economy in the world. We find that prices did converge to the law of one price in China for an overwhelming majority of goods and services, based on a large panel data set. The finding sheds light on the extent of the market economy in China, and casts doubt on Young's proposition that the economic reform has led to the fragmentation of Chinese domestic markets.